A window of one's own: a public office post-occupancy evaluation. Issue 4 (19th May 2019) - Meir, Isaac A.; Schwartz, Moshe; Davara, Yosefa; Garb, Yaakov
ABSTRACT: The prevalence of mechanical climatization in office buildings, alongside the dictate to conserve energy, has misguidedly promoted the construction of buildings with non-operable windows. Research shows that such buildings are detrimental to their occupants' wellbeing and productivity, sometimes causing them to feel overcooled or overheated. This post-occupancy evaluation illustrates such problems through the case study of a courthouse building in a hot arid environment. A strong association is shown between occupant satisfaction, building ventilation and sense of wellbeing at work. A positive correlation was found between satisfaction with personal control, and overall satisfaction survey results show that workers express a willingness to compromise future salary rises in order to receive operable windows. Key lessons for architects are discussed.